COST ACCOUNTING AND THE LAW. - Simon, Sidney I. (The Accounting Review, 1964)
Abstract Although studies have been made investigating the history and development of cost accounting, little attention has been given to the question of the understanding or acceptance of the subject by courts of law. This paper, therefore, summarizes its author's research in attempting to learn what has been the attitude of justice in the U.S., as gleaned from judicial opinions in court decisions, toward the concepts, principles and practices of cost accounting. The study has been limited largely to manufacturing costs, as much work has been done in other fields. Since volumes, for instance, have been written on costs and values in public utility rate-making, that area is not considered here. The definition and delineation of costs in military procurement cost-plus-fixed-fee contracts is not only determined by government regulations, but a satisfactory investigation into such costs has been made. The many court decisions involving the Robinson-Patman Act will only occasionally be referred to herein, as most of them are not truly pertinent to this research.